A new class of biological materials: Cell membrane-derived hydrogel scaffolds. (March 2019) - Fan, Zhiyuan; Deng, Junjie; Li, Peter Y.; Chery, Daphney R.; Su, Yunfei; Zhu, Pu; Kambayashi, Taku; Blankenhorn, Elizabeth P.; Han, Lin; Cheng, Hao
Abstract: Biological materials are superior to synthetic biomaterials in biocompatibility and active interactions with cells. Here, a new class of biological materials, cell membrane-derived hydrogel scaffolds are reported for harnessing these advantages. To form macroporous scaffolds, vesicles derived from red blood cell membranes (RBCMs) are chemically crosslinked via cryogelation. The RBCM scaffolds with a pore size of around 70 μm are soft and injectable. Highly biocompatible scaffolds are typically made of superhydrophilic polymers and lack the ability to encapsulate and release hydrophobic drugs in a controlled manner. However, hydrophobic molecules can be efficiently encapsulated inside RBCM scaffolds and be sustainedly released. RBCM scaffolds show low neutrophil infiltration after subcutaneous injection in mice, and a significantly higher number of infiltrated macrophages than methacrylate alginate (MA-alginate) scaffolds. According to gene expression and surface markers, these macrophages have an M2-like phenotype, which is anti-inflammatory and immune suppressive. There are also higher percentages of macrophages presenting immunosuppressive PD-L1 in RBCM-scaffolds than in MA-alginate scaffolds. Interestingly, the concentrations of anti-inflammatory cytokine, IL-10 in both types of scaffolds are higher than those in normal organ tissues. This study sheds light on cell membrane-derived hydrogels, which can actively modulate cells in unique ways unavailable to existing hydrogel scaffolds. Graphical abstract: Image 1